Influence of Dentin Hybridization on the Chromatic Alteration of Teeth caused by Endodontic Sealers - Chaves, Lucas S.; Decurcio, Daniel A.; Magalhães, Ana Paula R.; Chaves, Gustavo S.; Estrela, Lucas R. A. [UNESP]; Estrela, Cyntia R. A.; Estrela, Carlos (FapUNIFESP (SciELO), 2024)
This study evaluated the influence of dentin hybridization on coronary chromatic alteration of endodontically treated bovine teeth using different endodontic sealers and Portland cement. The 200 central incisors were endodontically treated using different materials (Sealapex, Bio-C Sealer, AH-Plus, Endofill, and Portland cement) and distributed according to the presence or absence of dentin hybridization. The teeth underwent colorimetric analysis using the Easyshade® spectrophotometer at four different times: determining the color of the dental substrate before root canal filling (RCF), 7 days, 60 days, and 180 days after RCF. The data were evaluated for normality and homogeneity by the Shapiro-Wilk and Levene tests. A two-way analysis of variance was performed, with Sidak's post-test for multiple comparisons. The significance level was 5%. Dentin hybridization influenced the coronary chromatic alteration of Sealapex® after 7 days and in Bio-C Sealer® and AH Plus® after 60 days. The AH Plus after 7 days obtained the highest ΔE* when hybridized, and the Endofill® obtained the highest ΔE* when not hybridized. The AH Plus after 60 days got the highest ΔE* when hybridized and non-hybridized. The Sealapex® after 180 days obtained the highest ΔE* when hybridized, and the AH Plus obtained the highest ΔE* when not hybridized. The studied root canal sealers behaved differently regarding coronary chromatic alteration, making it difficult to predict a particular behavior. All endodontic sealers caused clinically noticeable chromatic changes after 7 days, 60 days, and 180 days, regardless of hybridization.
Keywords: Dentin adhesives; endodontics; root canal filling; sealer; tooth color